Analisis Yuridis Turut Serta Melakukan Perkosaan Dan Pembunuhan Berencana(Studi Putusan Nomor 3/Pid.B/2017/PN.Cbn) - Devny Melyanta Antoneta Moeda; Deddy R. Ch. Manafe; Rosalind Angel Fanggi (Artemis Law Journal, 2026)
Criminal acts committed together, such as ganging up, assault, rape, and premeditated murder, require separate proof of each element of the crime. Therefore, the author conducted this study with the following objectives: 1) To determine and analyze the judge's considerations regarding the criminal acts of participating in ganging up, assault, rape, and murder based on trial facts. 2) To determine and analyze the imposition of life imprisonment based on the purpose of sentencing. This study uses a normative legal research type by examining laws and court decisions. The sources of legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials which are then analyzed descriptively qualitatively. The results of the study indicate that the panel of judges has actively considered the involvement of the defendant by paying attention to the elements of the criminal acts of rape and premeditated murder which have been proven through witness statements, evidence, and the defendant's statement. Although the elements of the crime of assault and assault have not been proven, the imposition of a life sentence does not reflect a balance between each of the crimes that have been proven, so that the objectives of punishment, both as retribution, general deterrence, and social rehabilitation, are not fully achieved.